Selenium and Computational Studies - de Sousa, Natália F.; Scotti, Luciana; Muratov, Eugene N.; Scotti, Marcus Tullius (Mini Reviews in Medicinal Chemistry, 2021)
Background: Organocalcogens are a class of organic compounds obtained by the synthesis experiments to include S, Se, or Te. Among the elements that comprise this class, Se is characterized as an essential mineral and nutrient for humans. Se has been widely studied in many aspects. Organic synthesis of organoselenides is used for obtaining new potential drug candidates and may be highly beneficial from the use of computational approaches to reduce time and cost of the experiments. Thus, the goal of our study is to evaluate the computational approaches used in the organoselenides research from 1999 to 2019. Methods: A literature review was performed by searching the database “Web of Sciences”. Results: Most of the theoretical studies included structural elucidation or structure-property analysis. We also found research regarding molecular docking approaches and Quantitative Structure-Activity Relationship (QSAR) studies. Conclusions: Computational studies have been widely applied to organoselenides. They demonstrated promising results and resulted in reduced the cost of research, increased efficacy, and, ultimately, novel organoselenides with desired properties.
Keywords: structure-based